PENGGUNAAN APLIKASI MOBILE KASIR BAGI UMKM DALAM MENINGKATKAN KUALITAS LAPORAN KEUANGAN - Almas, Salsabila; Khairiyah, Nurul Nazilah; Yuliana, Nurul; Fadhilah, Farah; Dewi, Marcella Mutiara (TRILOGI ACCOUNTING & BUSINESS RESEARCH, 2023)
Micro, Small, and Medium Enterprises (MSMEs) have an important role as the backbone of the country's economy. However, MSMEs actors do not understand the importance of preparing financial statements. The development of the industrial revolution 4.0 era has made innovations by making various technological developments. The mobile cashier application is a form of technological development in the accounting field that can assist MSMEs actors in compiling financial reports according to established standards. This study aimed to analyze the application of a mobile cashier application to help improve the quality of financial reports for MSMEs actors. The method used is the PIECES method. The assessment indicators include performance, information, economy, control, efficiency, and services. The results showed that the presence of a mobile cashier application helped them improve the quality of financial reports.Keywords: MSMEs, Mobile Cashier, PIECES Method, Quality of Financial Statements